(untitled) (Jurnal Kemanusiaan, 2022)
Exit survey plays an important role in keeping any programs in higher education institutions moving forward. The findings from the survey contain vital information to the school about what program learning outcomes or skills students think they have achieved after the program. This paper used an exit survey to assess the graduate students of Bachelor of Management (Marketing) in Azman Hashim International Business School (AHIBS), Universiti Teknologi Malaysia (UTM). Questions asked in the exit survey pertain to whether graduates feel they have gained skills such as application of disciplinary knowledge, integration and application of specific competencies, teamwork, problem solving and critical thinking, communication, ethics and integrity, life-long learning and information management, entrepreneurship and leadership. In addition, the survey includes student ratings of academic advisor contributions, teaching and learning, curriculum as well as academic resources and facilities in AHIBS UTM. The data was collected from 70 graduates who completed their study in second semester of the year 2019/2020 using Google form. According to the results, 90% of them felt they were competent in the skills needed for their future career. In addition, more than 90% of the students were satisfied with their academic advisor as well as teaching and learning activities in AHIBS UTM while 80% of the students found that the program curriculum was useful and adequate. However, lowest scores were found in the exit survey when asked about internet speed, classroom facilities and academic support staff in AHIBS UTM. Lastly, students provided suggestions to improve the quality of the program. Overall, the results have highlighted some essential areas of improvement for AHIBS UTM.